KARAKTER CITRA ARSITEKTURAL DAN DESKRIPSI TEMPAT WISATA BERBASIS PERSEPSI SWAFOTO - Try Dandy, Alvin; Kusuma, Hanson Endra; Nurdini, Allis; Purwani, Ofita (Nature : National Academic Journal of Architecture, 2023)
Selfie-oriented tourist destinations gained significant popularity among tourists and mass media in 2015. Selfie spot is the key attraction of these sites, which often takes inspiration from renowned landmarks and tourist destinations worldwide. This article explores the visual-architectural characteristics, the original reference of these selfie spots, and tourists’ perceptions regarding the selfie spots. The study is mixed methods research, consisting of qualitative and quantitative stages. In the qualitative stage, the data are collected through qualitative content analysis (QCA) of 15 videos gathered from a video-sharing platform and analyzed using QCA and open coding to identify the visual-architectural characteristics and tourists’ perceptions of selfie spots in the videos. In the quantitative stage, the data are collected through online questionnaires and analyzed using principal component analysis (PCA) and factor analysis (FA). This study finds that selfie spots show visual-architectural characteristics such as reference to foreign and romantic images. The study also finds that the selfie spots are described as either visually appealing or described faithfully in accordance with their actual shape and form.